Challenges in Implementing Poverty Alleviation Programmes in Southeast Asia: A Systematic Literature Review - Idris, Iskandar; Othman, Nooraini; Zakaria, Wan Normeza Wan (Journal of Human Capital Development (JHCD), 2025)
The Southeast Asia region has continued to put great effort towards the development of poverty alleviation initiatives. A lot of these efforts have led to rapid economic growth and targeted initiatives. However, certain inequalities still exist among these countries. Even though a lot of research has been carried out on economic trends or programme outcomes, less systematic attention to institutional, deeper governance, and structural barriers still persists to shape the implementation of these programmes. Based on this, there is a need for a deeper understanding of both comparative and formulation of strategies to mitigate poverty in an integrated manner across the Southeast Asia region. As such, the current research addressed this gap by carrying out a systematic literature review of 20 peer-reviewed articles published between 2020 and 2024. The study’s findings identified four main themes and eight sub-themes to reveal the consolidated current regional scenarios and recurring challenges faced. Furthermore, the result showed the contextual as well as broader institutional conditions that affected sustainability and programme delivery rather than merely programme results. The present study concludes that the Southeast Asia poverty reduction requires more than policy expansion or economic growth but strategic approaches that enhance institutional capacity, strengthen governance, and build resilience that mitigate shocks, as well as maintain diverse contexts of the region. The findings contribute to practical guidance for policymakers and academic debate on pursuing more sustainable and inclusive poverty strategies.